Gas chromatographic isolation of individual compounds from complex matrices for radiocarbon dating - Eglinton, T. I.; Aluwihare, L. I.; Bauer, J. E.; Druffel, E. R.; McNichol, A. P. (Anal Chem, 1996)
This paper describes the application of a novel, practical approach for isolation of individual compounds from complex organic matrices for natural abundance radiocarbon measurement. This is achieved through the use of automated preparative capillary gas chromatography (PCGC) to separate and recover sufficient quantities of individual target compounds for (14)C analysis by accelerator mass spectrometry (AMS). We developed and tested this approach using a suite of samples (plant lipids, petroleums) whose ages spanned the (14)C time scale and which contained a variety of compound types (fatty acids, sterols, hydrocarbons). Comparison of individual compound and bulk radiocarbon signatures for the isotopically homogeneous samples studied revealed that Delta(14)C values generally agreed well (+/-10%). Background contamination was assessed at each stage of the isolation procedure, and incomplete solvent removal prior to combustion was the only significant source of additional carbon. Isotope fractionation was addressed through compound-specific stable carbon isotopic analyses. Fractionation of isotopes during isolation of individual compounds was minimal (<5 per thousand for delta(13)C), provided the entire peak was collected during PCGC. Trapping of partially coeluting peaks did cause errors, and these results highlight the importance of conducting stable carbon isotopic measurements of each trapped compound in concert with AMS for reliable radiocarbon measurements. The addition of carbon accompanying derivatization of functionalized compounds (e.g., fatty acids and sterols) prior to chromatographic separation represents a further source of potential error. This contribution can be removed using a simple isotopic mass balance approach. Based on these preliminary results, the PCGC-based approach holds promise for accurately determining (14)C ages on compounds specific to a given source within complex, heterogeneous samples.
Eglinton, T IAluwihare, L IBauer, J EDruffel, E RMcNichol, A Peng1996/03/01 00:00Anal Chem. 1996 Mar 1;68(5):904-12. doi: 10.1021/ac9508513.